Evaluation of hemp seeds (Cannabis sativa L.) and flax seeds (Linum usitatissimum L.) as feed ingredients in laying hen diets: effects on the performance, egg quality, and n-3 fatty acid composition of egg yolks - Szmek, Jan; Englmaierová, Michaela; Skřivan, Miloš; Pěchoučková, Eva (Frontiers in Animal Science, 2025)
Hemp seed (HS) and flax seed (FS) are natural sources of bioactive compounds, including n-3 polyunsaturated fatty acids (PUFAs). The aim of this study was to investigate the effects of HS from the non-psychoactive variety Futura, non-extruded FS from the variety Floral, and their combination on the performance of laying hens and the quality and nutritional profile of the eggs produced. A total of 240 Lohmann Brown laying hens were randomly allocated to 4 dietary treatments, with 6 replicate cages and 10 hens per cage. The first (I) control diet contained no seed supplementation. The second (II) and third (III) diets were supplemented with 40 g/kg FS and 40 g/kg HS, respectively. The fourth (IV) diet included a combination of HS and FS (both at 40 g/kg). The inclusion of FS significantly increased both egg production and egg mass (p < 0.001). The lowest feed conversion ratio was observed in group II, which received FS alone. The addition of HS increased feed consumption per egg (p = 0.005) and total egg mass (p < 0.001). All the seed-supplemented groups exhibited increased egg weights. HS supplementation markedly increased yolk γ-tocopherol concentrations (p < 0.001) and reduced total cholesterol (p = 0.042) and malondialdehyde levels in fresh yolks (p = 0.003), indicating a potential improvement in oxidative stability. The combined supplementation with HS and FS (IV) significantly increased the total PUFA content (p = 0.004), including both n-6 (p < 0.022) and n-3 (p = 0.001) PUFAs. Among the n-3 PUFAs, the levels of α-linolenic and eicosapentaenoic acids were elevated. These changes contributed to an improved n-6/n-3 ratio, which was significantly affected by both HS and FS supplementation (p < 0.001). All dietary treatments significantly improved the lipid quality indices (p < 0.001). These findings highlight the potential of HS and FS as functional feed ingredients, with FS mainly enhancing hen performance and HS improving the nutritional quality of eggs through bioactive compound enrichment.